Report of the expert group meeting on using universal service funds to increase access to technology for persons with disabilities - NU. CEPAL. Sede Subregional para el Caribe (ECLAC, Subregional Headquarters for the Caribbean, 2019)
Summary of recommendations. -- Attendance and organization of work. -- Summary of proceedings.